Effectiveness of sealing gel on vertical misfit at the implant-abutment interface and preload maintenance of screw-retained implant-supported prostheses - Seloto, Camila Berbel [UNESP]; Strazzi-Sahyon, Henrico Badaoui [UNESP]; dos Santos, Paulo Henrique [UNESP]; Assunção, Wirley Gonçalves [UNESP] (Quintessence Publishing, 2020)
Purpose: This in vitro study evaluated the effectiveness of a sealing agent on v: ertical misfit of the implant-abutment interface in an external hexagon implant system before and after mechanical cyclic loading. Effects on preload maintenance of retaining screws after mechanical cycling were also assessed. Materials and Methods: External hexagon implant systems were divided into two groups (n = 12) according to the presence of an anaerobic sealing gel (control group-no sealing gel; experimental group-sealing gel applied). A prefabricated UCLA abutment was attached to the external hexagon implant with a digital torque wrench in accordance with the recommendations of the manufacturer. Specimens were tested through mechanical cyclic loading (1 × 106 cycles, 2 Hz, and 130 N). Vertical misfit of the implant-abutment interface was analyzed using a stereomicroscope, and reverse torque values were obtained using a digital wrench. Misfit and reverse torque data were measured and analyzed via analysis of variance (ANOVA) and the Tukey least significant difference test (α = .05). Results: The sealing gel promoted lower vertical misfit values in the test group after mechanical cycling compared with before cycling (P = .009). The control group showed lower reverse torque values for retaining screws compared with the initial torque after mechanical cyclic loading (P < .0001). However, sealing gel application promoted higher reverse torque values in the test group postcycling (P = .0003). Conclusion: Anaerobic sealing agent application improved vertical misfit of the implant-abutment interface and preload maintenance of screw-retained implant-supported prostheses post- mechanical cycling.
Keywords: Abutment; Implant-supported prosthesis; Preload; Screw